National prosecutions as the main remedy in cases of massive human rights violations: an assessment of the approach of the European Court of Human Rights - Răduleţu, Sebastian (International journal of transitional justice, 2015)
The phenomenon of massive human rights violations has created a preoccupation among states and within the international community with how these acts should be remedied in a human rights context. The focus of this article is the European Court of Human Rights’ role in scrutinizing domestic investigations and prosecutions of massive human rights violations. It asserts that while the Court, for various reasons, has taken a rather conservative approach, it has nonetheless succeeded in developing a doctrine of procedural obligations under Articles 2, 3 and 5 of the European Convention on Human Rights and in removing juridical obstacles to domestic prosecutions, such as amnesty laws or non-retroactivity penal norms. This article also maintains that because the central role in supervising the execution of the Court’s judgments belongs to the Committee of Ministers of the Council of Europe, a political body, the Court’s decisions in cases of widespread and systematic abuse could provide a strong foundation for both political pressure and political measures against reluctant states.